Power density analysis and multi-objective optimization for a modified endoreversible simple closed Brayton cycle with one isothermal heating process. (November 2020) - Tang, Chenqi; Feng, Huijun; Chen, Lingen; Wang, Wenhua
Abstract: By using finite time thermodynamics, a modified endoreversible simple closed Brayton cycle with one isothermal heating process and variable isothermal pressure drop ratio is established in this paper. The cycle is composed of a compressor, a regular combustion chamber, a converging combustion chamber, a turbine and a precooler. Three variable temperature heat reservoirs are considered. The dimensionless power density is selected as the optimization objective, and the effects of inlet temperature ratios of combustion chambers on the optimal performances are studied. The results show that adding a convergent combustion chamber to the cycle can increase the dimensionless power density by 18.57%. There exit the optimal heat conductance distributions among three heat exchangers and the optimal pressure ratio leading to maximum dimensionless power density. The Pareto front based on dimensionless power output, thermal efficiency and dimensionless power density is further obtained by applying NSGA-II algorithm, and three decision methods are employed to choose the appropriate schemes from Pareto front. The different optimization schemes gained in this paper can satisfy different design demands for practical Brayton cycle power plants. Highlights: Modified endoreversible closed Brayton cycle is built. Finite time thermodynamics is used in this paper. It is with variable temperature heat reservoirs. It is with an isothermal heat process and variable isothermal pressure drop ratio. It includes a compressor, two combustion chambers, a turbine and a precooler. Optimal heat conductance distributions and pressure ratio are obtained. Pareto front based on power output, efficiency and power density is obtained.